Pathways to thinking schools - Hyerle, David N.; Alper, Larry (Thousand Oaks, California : Corwin, a SAGE Company, 2014)
Based on the successful, proven Thinking Maps model developed by David Hyerle, this book makes a compelling case for making an explicit focus on thinking the foundation for every school. Enabling all students to become drivers of their own thinking and learning, a Thinking School is defined as an educational community in which all members share a common commitment to giving regular, careful thought to everything that takes place including learning how to think reflectively, critically and creatively. -- Provided by publisher.
Includes bibliographical references and index.
Keywords: Thought and thinking -- Study and teaching; Visual learning; Educational leadership; School management and organization